Serial Troponin for Early Detection of Nivolumab Cardiotoxicity in Advanced Non‐Small Cell Lung Cancer Patients. (23rd March 2018) - Sarocchi, Matteo; Grossi, Francesco; Arboscello, Eleonora; Bellodi, Andrea; Genova, Carlo; Dal Bello, Maria Giovanna; Rijavec, Erika; Barletta, Giulia; Rossi, Giovanni; Biello, Federica; Ghigliotti, Giorgio; Canepa, Marco; et al.
Abstract : Background: Rare cases of severe myocarditis are reported during treatment with nivolumab. Troponin, a biomarker of cardiac damage, is a key component of the diagnostic workup of many cardiac disorders, including myocarditis. This study investigates the role of troponin to assess cardiac involvement during nivolumab therapy for non‐small cell lung cancer (NSCLC). Materials and Methods: We evaluated 59 NSCLC patients, analyzing serum samples collected within a translational research study. Troponin above the upper normal limit (0.046 ng/mL) was defined as Tn+, whereas normal but detectable troponin (0.015–0.045) was defined as Tn det . Troponin alterations were interpreted on the grounds of the following elements: peak values and time curve, cardiac comorbidities, signs and symptoms coincident to troponin elevation, ECG, echocardiography, and disease progression. Results: No patient had cardiovascular events. Among 362 available blood samples, Tn+ (max 0.317 ng/mL) was found in 13 determinations belonging to 6 patients. Seven other patients had isolated Tn det . In five patients, Tn+ was attributed to cardiac comorbidities, disease progression, or worsening clinical status. One patient without cardiac history and in good clinical condition had a sustained troponin increase—soon after the start of therapy—and after careful evaluation of all relevant elements, it was interpreted as a marker of nivolumab‐related subclinical myocarditis. Conclusion: Tn+ may occur in NSCLC patients treated with nivolumab, but in most cases it does not indicate nivolumab cardiotoxicity. In some cases, however, a careful interpretation of troponin alteration, especially at the beginning of therapy, enables identification of subclinical myocarditis, thus allowing early cardiac treatment. Implications for Practice: Myocarditis is a rare but serious adverse event of immune checkpoint blockade with nivolumab, which needs to be recognized as soon as possible. This article suggests that troponin, a user‐friendly biomarker of myocardial cytotoxicity, might be useful for early detection of immune‐mediated myocarditis. However, because troponin abnormalities might also be related to a number of conditions capable of causing myocardial oxygen demand‐supply mismatch, a careful cardiac assessment should be performed in non‐small cell lung cancer patients in order to properly interpret any troponin increase. According to the available evidence, monitoring troponin during the first weeks of treatment can be considered reasonable. Abstract : This article explores the potential role of seriated troponin assessments during treatment with nivolumab for advanced non‐small cell lung cancer as a biomarker of nivolumab‐related cardiac toxicity.